Optimization of agricultural supply chain through a crop distribution center for economic empowerment towards a smart city - Degus Satya Mudana; Aulia Mutz Vira; Vyola Cecilia Potto; Rizal Adi Saputra (Journal of Agrosociology and Sustainability, 2026)
Background: The agricultural sector is vital to Indonesia's economy, yet farmer welfare remains low due to long, inefficient distribution chains that limit their income and create dependency on intermediaries. High poverty rates and a lack of formal protection plague farming households, preventing them from receiving fair economic value for their products. This study aims to design and develop a digital solution that positions farmers as key players in the agricultural supply chain, breaking their dependence on conventional systems. Methods: This research utilized a combined methodological approach, integrating Research and Development (R&D) to design the innovation and the Waterfall model for the structured development of the digital system. Data collection was performed using a mixed-methods approach, involving quantitative surveys to assess farmers' needs and qualitative interviews to understand supply chain challenges. Findings: The primary outcome is an integrated digital marketplace and physical crop distribution center. This system enables direct B2C (Business-to-Consumer) sales from farmers to consumers, with proceeds transferred immediately to their accounts. The application prototype was tested with target users, achieving a high success rate of 83.33% based on the System Usability Scale (SUS), which validates the design's effectiveness and intuitive user experience. Conclusion: The integrated platform represents a feasible solution to improve farmers' market access and agricultural distribution. The high usability score demonstrates its potential to support an inclusive and sustainable smart economy. Novelty/Originality of this article: The novelty of this research lies in its integrated ecosystem approach, which combines a physical distribution hub (for logistics, storage, and quality control) with a direct-to-consumer digital marketplace. This holistic model directly addresses both the logistical and market access barriers for farmers, offering a comprehensive solution that distinguishes it from existing platforms focused solely on digital transactions.